Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.

Botanic analysis of Livia's villa painted flora (Prima Porta, Roma) (JOURNAL OF CULTURAL HERITAGE, 2003)
The frescoes of Livia's villa at Prima Porta, Rome, are the most famous representations of Roman gardens. The painted flora is analyzed from the scientific viewpoint and previous identifications are critically discussed. Here, 24 different species are described, giving information on the taxonomic, and phytogeographic position. Most of them belong to the spontaneous elements present in the Mediterranean forests, maquis and grasses of Southern Italy, such as Arbutus unedo, Laurus nobilis, Nerium oleander, Quercus ilex, Quercus robur gr., Comas mas, Myrtus communis, Phyllitis scolopendrium, Viola reichenbachiana, Chrysanthemum coronarium, Anthemis cotula, or widely cultivated, such as Cupressus sempervirens. cydonia oblonga, Pinus pinea, Punica granatum, Papaver somniferum, Rosa centifolia, Phoenix dactylifera. A symbolistic purpose of the pictures is also clearly evident. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.